Trobriand Gender Identity - Montague, Susan P. (The Australian journal of anthropology, 1983)
This paper explores both the substantial and non-substantial qualities that comprise Trobriand gender. Among other issues it investigates how complicated adult gender creates a situation that makes life fair and equitable between the sexes.